Characterization of Sepaku Clay Shale with Slaking Test, X-Ray Diffraction and Scanning Electron Microscopy: Potential Stabilization Using Bacillus Subtilis - Yuswal Subhy; Achmad Bakri Muhiddin; Ardy Arsyad (Indonesian Geotechnical Journal, 2025)
Clay shale in the Sepaku region exhibits geotechnical vulnerability (slaking, cohesion loss, saturation expansion) that threatens slope stability and road foundations. Conventional stabilization methods (cement/lime) can cause negative environmental impact; therefore, alternatives with low environmental impact such as microbially induced carbonate precipitation (MICP) are sought for. MICP has the potential to improve the mechanical properties of clay shale. MICP utilizes microbial activity (urease enzyme or alternative pathways) to trigger CaCO3 precipitation that binds soil particles and fills pores. In order to optimize the stabilization effects of MICP on Sepaku clay shale, it is first necessary to characterize the clay shale properties. Slaking test, X-Ray diffraction and scanning electron microscopy were conducted on clay shales samples obtained from Sepaku region. The SPT tests from two boreholes show NSPT values of above 60 for the shale, which is expected for unweathered shale. The disturbed samples were then subjected to slaking tests, which the results categorize the shale to be low durability after one cycle of wetting and drying, and very low durability after two cycles of wetting and drying. The unconfined compressive strength was found to be 2.53 MPa, categorizing the Sepaku clay as weak rock. The XRD and SEM results of Sepaku clay revealed consistent values and characteristics as other clay shales. This research serves as preliminary investigation to optimize the stabilization of Sepaku clay shale using MICP method, in particular Bacillus Subtilis bacteria.